DISCOURSE FUNCTIONS OF LECTURER CODE-SWITCHING IN ESP CLASSROOMS: A CASE STUDY IN BAROMBONG MERCHANT MARINE POLYTECHNIC - Khafifah; Muhammad Iqbal (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
Effective classroom Communication is essential, particularly in English for Specific Purposes (ESP), where language and technical knowledge must be integrated. However, the functional role of lecturer code-switching in an ESP classroom remains underexplored, particularly in vocational contexts where communication directly supports professional readiness. This study aims to investigate the discourse functions of lecturer code-switching in an  ESP classroom at Barombong Merchant Marine Polytechnic. A qualitative case study design was employed, with data collected through classroom observations, interviews, audio recordings, field notes, and reflective journals. The data were analyzed using Miles and Huberman's interactive model, including data condensation, data display, and conclusion drawing and verification. This study contributes by extending code-switching research into an ESP context and addressing the need for effective instructional communication in vocational education. The findings revealed six key discourse functions of lecturer code-switching: (1) encouraging student responsiveness, (2) managing classroom activities, (3) explicating content explanations, (4) giving clear instructions, (5) clarifying difficult points, and (6) correcting student errors. These functions served to bridge comprehension gaps, support classroom management, and enhance student engagement in English for Specific Purposes (ESP) learning. In conclusion, code-switching functions as a strategic pedagogical tool that enhances comprehension, classroom interaction, and instructional effectiveness in ESP classrooms.